Identifying Contextual Factors That Informed Planning and System Development for School-Based Tokyo 2020 Olympic and Paralympic Education: A Realist Evaluation. Issue 18 (26th April 2022) - Hwang, Bora; Miyazaki, Akiyo; Henry, Ian
Abstract: The role and significance of Olympic and Paralympic education has become increasingly evident in the activities of Olympic and Paralympic host cities. The development of Olympic and Paralympic education as a compulsory element has become a key policy aim for host cities and nations, with long-term planning and strategies needed for successful delivery. However, there remains a paucity of studies assessing the ways of planning and developing Olympic and Paralympic education mediated by contextual factors. Tokyo 2020 Olympic and Paralympic education has been implemented in schools nationwide as a national campaign and represents the first occasion in which Paralympic education is promoted in parallel with Olympic education. This study conducted a realist evaluation to analyse the history of education and sport policy in Japan, thus identifying contextual factors that informed planning and system development issues for school-based Tokyo 2020 Olympic and Paralympic education. This study suggests a methodological approach to identifying and evaluating contextual elements and mechanisms that are relevant in the development of Olympic and Paralympic education.